New Polyene Antifungal Antibiotic Produced by a Species of Actinoplanes - Wagman, G. H. (1975)
A new species of Actinoplanes, which has been deposited with the designation NRRL 5325 at the Northern Utilization Research and Development Division of the U. S. Department of Agriculture, produces a polyene antifungal complex designated as Sch 16656. The complex, consisting of one major and three minor components, is isolated from the fermentation broth by a solvent extraction procedure and purified by precipitation methods. The major component is a heptaene and is highly active in vitro and in vivo against Candida albicans. It is active also against strains of Torulopsis and is significantly more potent orally than candicidin in mice against Candida infections.